1988
DOI: 10.2151/jmsj1965.66.6_967
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Surface Air Temperature over Japan and the Global Sea Surface Temperature

Akio Kitoh

Abstract: Relationships between the global sea surface temperature (SST) and the surface air temperature over Japan (TsJ) are examined by computing lagged cross-correlations based on the monthly mean data for [1970][1971][1972][1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983][1984]. High correlation is found between the TsJ for December and the preceding SST over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Recently, many authors have pointed out that during an El Nino/Southern Oscillation (henceforth, ENSO) event, sea surface temperature (SST) in the mid-and high-latitudes of the North Pacific varies coherently with that in tropical region to some extent (e.g., Iwasaka el al., 1987, henceforth IHT1 ;Hanawa el al., 1988, HWIST ;Kawamura, 1988 ;Yasunari, 1987aYasunari, , b, 1988Kitoh, 1988b). Among them, HWIST showed that during an ENSO event, positive SST anomalies in the ENSO year winter, i, e., winter during an ENSO event (e.g., January through March of 1983 for the 1982/83 ENSO event) appear in a wide tonal band along 30*N line, extending from the Asian coast to near 170*E, as shown ©1989, Meteorological Society of Japan in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many authors have pointed out that during an El Nino/Southern Oscillation (henceforth, ENSO) event, sea surface temperature (SST) in the mid-and high-latitudes of the North Pacific varies coherently with that in tropical region to some extent (e.g., Iwasaka el al., 1987, henceforth IHT1 ;Hanawa el al., 1988, HWIST ;Kawamura, 1988 ;Yasunari, 1987aYasunari, , b, 1988Kitoh, 1988b). Among them, HWIST showed that during an ENSO event, positive SST anomalies in the ENSO year winter, i, e., winter during an ENSO event (e.g., January through March of 1983 for the 1982/83 ENSO event) appear in a wide tonal band along 30*N line, extending from the Asian coast to near 170*E, as shown ©1989, Meteorological Society of Japan in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…are chosen to fully describe the Southern Oscillation. The SST anomaly at 0°N, 160°W has the highest simultaneous correlation with the SOI in the real atmosphere (Kitoh, 1988).…”
Section: Observed Datamentioning
confidence: 94%
“…The central equatorial Pacific SST maintains a high correlation with the central and eastern equatorial Pacific SST for ±6 months. This high persistence reflects the fact that the SST anomaly in this region tends to form around boreal early summer, persist throughout autumn and winter until it tends to change its sign in boreal spring (Wallace and Jiang, 1987;Kitoh, 1988). The western equatorial Pacific SST tends to correlate negatively with the central equatorial Pacific SST, but the correlation coefficient is small and insignificant.…”
Section: Lag-correlationsmentioning
confidence: 99%
“…Except for this season, the Nino3 SSTA can be predicted with a certain skill (Latif and Graham, 1991), and has a high auto-correlation until almost the next spring (see Fig. 6 of Kitoh, 1988). Tomita and Yasunari (1993) classified the ENSOs into the two types of the BO-ENSO and the LF-ENSO by occurrence duration.…”
Section: Scs and Change Of Nino3 Sstamentioning
confidence: 99%